2014
DOI: 10.1177/0022487114535266
|View full text |Cite
|
Sign up to set email alerts
|

What Should Teacher Educators Know and Be Able to Do? Perspectives From Practicing Teacher Educators

Abstract: Commonsense reasoning says that quality teacher education relies on quality teacher educators. Yet, there is minimal attention to what teacher educators should know and be able to do. Unquestionably, teacher educators cannot teach what they do not know; but what should they know, and should they be prepared? This study of 293 teacher educators investigated the following: What do current teacher educators consider to be the foundation elements of their practice? How do they evaluate their own preparation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
12

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(154 citation statements)
references
References 38 publications
4
120
0
12
Order By: Relevance
“…If that context does not enhance sustainability, why should the graduated teachers be ready to take such steps when they start working in schools? In their study of teacher educators, Goodwin et al [63] found that teacher educators realized that their work relates to the larger contexts in which it is situated. A quarter of the respondents saw it as challenging to navigate among agendas and policies at the universities, since these agendas are often in conflict with their own view of their work.…”
Section: Sustainability In Policy Documentsmentioning
confidence: 99%
See 1 more Smart Citation
“…If that context does not enhance sustainability, why should the graduated teachers be ready to take such steps when they start working in schools? In their study of teacher educators, Goodwin et al [63] found that teacher educators realized that their work relates to the larger contexts in which it is situated. A quarter of the respondents saw it as challenging to navigate among agendas and policies at the universities, since these agendas are often in conflict with their own view of their work.…”
Section: Sustainability In Policy Documentsmentioning
confidence: 99%
“…As Goodwin et al have pointed out, "Quality teacher education relies on quality teacher educators" [63] (p. 284). Therefore it is important to investigate teacher educators' views on sustainability and the implementation of sustainability in their work.…”
Section: Sustainability In Teacher Educationmentioning
confidence: 99%
“…They face tensions regarding their identities (Williams, Ritter, & Bullock, 2012) that consequently influence their work. In university settings, TEs may be hired for their content or discipline knowledge, with little or no attention paid to their knowledge of teacher educating methods (Goodwin et al, 2014).…”
Section: Tes As Self-regulatory Professionalsmentioning
confidence: 99%
“…The studentcentered learning of environmental exploration may be conducted using active-and cooperativebased strategies. Therefore, teachers should support, supervise and guide students to achieve the desired competencies (Goodwin et al, 2014). (Williams, 2014) added that there are three teacher essential dimensions in the teaching and learning process; that is, (1) managing the teachers conception relating to personal identity, (2) identifying the perspective change related to the teaching and learning process, (3) negotiating complex professional relationships associated with learning.…”
Section: The Prototype Of Lesson Design and Workbooksmentioning
confidence: 99%